Rural Social Transformation in the Digital Era: The ABCD Approach as a Catalyst - Wildan Miftahussurur; Silfin Aisyah (Jurnal Realitas Sosial, 2025)
This study aims to describe and analyze the integration of the Asset-Based Community Development (ABCD) approach with digitalization in the social and economic empowerment of rural communities, specifically in Ledokombo Village, Jember Regency. A qualitative descriptive approach was employed, with data collected through participatory observation, in-depth interviews, and documentation studies. The findings indicate that the ABCD approach effectively identifies and mobilizes local assets, including individual skills in traditional food processing, social capital through community networks, and cultural values that strengthen village identity. This approach builds a strong social foundation, increases active community participation, and fosters the formation of working groups for MSME coordination. Digitalization acts as an empowerment accelerator through the use of Google Maps, Geographic Information Systems (GIS), and digital literacy. All MSMEs are registered online, customer interactions have increased, and spatial mapping enables data-based planning. The tangible impacts of this integration include a 30–50% increase in MSME revenue, expanded market access beyond the district, and strengthened social networks and digital inclusion. The synergy between ABCD and digitalization creates a hybrid empowerment model that not only enhances local economic capacity but also strengthens social cohesion and community readiness to face global challenges. This study demonstrates that asset-based empowerment strategies combined with technological innovation can serve as an inclusive, sustainable, and contextual rural development model for other villages in Indonesia, while contributing to improved social and economic well-being in the digital era.